Understanding and implementing environmental management in small entrepreneurial ventures: supply chain management, production and design - Amorim, Paula Gonçalves [UNESP]; Mathias, Maria Augusta Siqueira [UNESP]; Rocha, Aglaé Baptista Torres da [UNESP]; Oliveira, Otávio José de [UNESP] (Emerald, 2023)
Purpose: This work aims to propose guidelines for small industrial businesses to take their first steps toward implementing systems, programs and tools (SPTs) for environmental management in a structured way. Design/methodology/approach: The authors conducted case studies in large companies certificated ISO 14001. They ran tests for construct validity, external validity and reliability. Cross-analysis of the information collected led to identifying patterns and strategies adopted by these companies to implement environmental management. Based on the literature on environmental management in small businesses and the author's experience, the practices learned from large companies were adapted to the reality of small ones, thus resulting in the proposed guidelines. Findings: These guidelines enable small companies to develop their environmental management following the logical evolution of SPTs: ISO 14001, green supply chain management (GSCM), cleaner production (CP) and green design (GD). The implementation should happen gradually, through the PDCA cycle, according to three specific levels of environmental evolution. Research limitations/implications: Since the guidelines focused on small industrial companies, future studies should consider other sectors, such as services, to benefit from the solutions presented. As for the implications, besides improving the small company's performance and enhancing its image, implementing the guidelines creates a green synergy along the supply chain, thus benefiting society beyond the company's borders. Originality/value: The main theoretical-scientific contribution of this work is to deepen a block of knowledge that articulates environmental management and small businesses, creating a basis for further research and a reference for analyzing and discussing empirical studies in small companies. As an applied-management contribution, the guidelines allow small companies to effectively develop SPTs to move toward environmental sustainability.
Keywords: Design; Environmental management; Guidelines; Production; Small companies; Small entrepreneurial ventures; Small industrial businesses; Supply chain management